SEG Technical Program Expanded Abstracts 2013 2013
DOI: 10.1190/segam2013-0761.1
|View full text |Cite
|
Sign up to set email alerts
|

Gas shale; Comparison between permeability anisotropy and elasticity anisotropy

Abstract: The studied Gas Shale especially the silica-rich gas-shale samples displayed permeability and elasticity anisotropy behavior. These anisotropy behaviors are closely correlated in terms of the symmetry directions which means the elastic anisotropy and permeability anisotropy share the same cause. All samples, regardless of the measurement direction, show a nonlinear reduction in permeability with increase of effective pressure (up to 3 orders of magnitude), with large variations from sample to sample and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Sakhaee-Pour and Bryant (2012) analyzed numerically the effect of a gas adsorbed layer and of gas slippage at pore walls on the flow behavior in individual conduits of simple geometry and in a network of such conduits. Shale formations compose of thinly layered sequences of aligned microscopic clay platelets, and exhibit highly anisotropic in permeability and elasticity (Metwally et al, 2013, Jin et al, 2014. Al Ismail et al (2014) observed the permeability anisotropy in the measurements on the horizontal (cut parallel to the bedding) and vertical (cut normal to the bedding) samples.…”
Section: Introductionmentioning
confidence: 99%
“…Sakhaee-Pour and Bryant (2012) analyzed numerically the effect of a gas adsorbed layer and of gas slippage at pore walls on the flow behavior in individual conduits of simple geometry and in a network of such conduits. Shale formations compose of thinly layered sequences of aligned microscopic clay platelets, and exhibit highly anisotropic in permeability and elasticity (Metwally et al, 2013, Jin et al, 2014. Al Ismail et al (2014) observed the permeability anisotropy in the measurements on the horizontal (cut parallel to the bedding) and vertical (cut normal to the bedding) samples.…”
Section: Introductionmentioning
confidence: 99%